Artificial Intelligence and the Academic Honesty Crisis: A Critical Study of AI Chatbot Use in Students' Academic Assignments - Amak Fadholi; Sauqi Futaqi; Muhtadi Ridwan (Perkumpulan Dosen Tarbiyah Islam Indonesia, 2026)
This study aims to critically analyze the disruption of generative artificial intelligence (GenAI) technologies on the academic integrity crisis among higher education students and to propose a new adaptive evaluation framework. The research methodology employed is library research with a critical study approach. Data collection was conducted through a systematic digital search protocol across indexed scientific databases for literature published between 2021 and 2026. The gathered secondary qualitative data were then analyzed using qualitative content analysis techniques. The results indicate a radical shift in how students utilize AI chatbots, mutating from tools for conceptual brainstorming (cognitive augmentation) into shortcuts for instant assignment completion (cognitive outsourcing). This phenomenon has triggered a new form of academic dishonesty termed